Determining Distribution Vehicle Routes to Reduce Distribution Costs Using Sequential Insertion Method at PT. XYZ - Sumiati; Sinta Dewi; Isna Nugraha (Nusantara Science and Technology Proceedings)
VRP is concerned with determining routes for problems involving more than one vehicle with a certain capacity to serve consumers with their respective requests. Route determination is one of the important factors in delivering products to consumers. Determining the optimal distribution route can minimize distance, shorten product delivery time and save transportation costs. PT. XYZ is a company engaged in the distribution of consumer goods. Problems that are happening at PT. XYZ is a product distribution problem where the number of vehicles is limited. The number of customers and the distance from the depot to the customer and from one customer to another is far away. Therefore, it is necessary to determine distribution routes, especially in transportation problems, to save time, distance, and distribution costs. The objectives to be achieved from research at PT. XYZ is to determine the product distribution route using the Sequential Insertion method. Based on the data processing results, the route Sequential Insertion method can serve customers in 5 routes with a total distance of 227.8 km, a total travel time of 15.9 hours, and a total distribution cost of IDR 145,792/week. The travel distance savings are 28.20 km, and the percentage of distribution cost savings is 11%, or the distribution cost savings are IDR 866,304/year. So, the Sequential Insertion method can be applied to determine the optimal distribution route to produce a minimum distribution cost